Perlindungan Korban Kekerasan dalam Rumah Tangga (KDRT) dalam Perspektif Viktimologi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Domestic Violence (Kekerasan Dalam Rumah Tangga/KDRT) is a complex social phenomenon that requires continuous legal and social attention. In the context of Indonesia, the protection of domestic violence victims has been regulated under Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which affirms that victims are entitled to protection, recovery, and legal assistance. However, the implementation of these protections faces several structural and cultural obstacles, such as social stigma against victims, limited human resources, and the influence of patriarchal culture that legitimizes violence within the household. Using normative legal research methods with statutory and conceptual approaches, this article analyzes the policy framework for the protection of domestic violence victims in Indonesia, as well as the roles of government and non-government institutions in providing such protection. The results of this study show that although the legal protection of domestic violence victims is clearly regulated, its implementation in practice remains suboptimal due to social and structural barriers. Therefore, strong legal policies must be supported by the synergy of law enforcement institutions, social organizations, and community participation to ensure effective and sustainable protection for victims. These findings are expected to contribute to the formulation of future policies that are more responsive to the protection of the rights of domestic violence victims.